Design and Analysis of Weak Inversion Low Power Operational Amplifier - Jagtap, Amit (My University, 2008)
The main objective of this dissertation is to elaborate performance difference in terms of power dissipation, gain, bandwidth and slew rate of weak inversion op-amp compared to bulk driven and floating gate low power op-amp in literature. Also design approach is compared against conventional design procedure for the design of weak inversion operational amplifier. The approach is more accurate as it covers all transistor operating regimes, reducing the number of electrical parameters related to the fabrication process. In weak inversion topology transistor operates below strong inversion region. In this region is very high, which gives high gain as compared to that of bulk driven and floating gate topology. In present work, a simple two stage weak inversion opamp is designed using TSMC 0.35 technology with a supply voltage of 3.3V. The power dissipation of the opamp is 3.174 with unity gain bandwidth of 160.79 and phase margin of . Further process corner simulations have been done for process variation of 20% in threshold voltage , oxide thickness and mobility .
Keywords: Operational Amplifier; Low power; Weak Inversion; Bulk Driven; Gm-Id Approach